THE IMPACT OF THE "THINK-PAIR-SHARE" STRATEGY ON MOTOR SATISFACTION AND LEARNING THE TENNIS SERVE SKILL AMONG STUDENTS (CAHIERS MAGELLANES-NS, 2024)
By closely observing most educational units related to tennis, the researchers noted that many teachers rely on direct methods to deliver educational content, with the predominant approach being the command style. This method often lacks the use of modern strategies and techniques, which may be more effective in learning and acquiring motor skills, especially the tennis serve skill, which could lead to students feeling more satisfied with their performance of this skill. The research aimed to identify the impact of the "Think-Pair-Share" strategy on motor satisfaction and learning the tennis serve skill among students. The research community was identified as third-year students in the Faculty of Physical Education and Sports Sciences at Al Ain University for the academic year 2023-2024, with a total of 141 students. The research sample was randomly selected by lottery, consisting of 28 students from two groups (B and C). They were then divided into two groups: a control group and an experimental group, with 14 students in each group. The control group followed the teacher's method, while the experimental group followed an educational method based on the "Think-Pair-Share" strategy. The researchers found that the "Think-Pair-Share" strategy significantly improved the skill performance level of the tennis serve among the experimental group members